Soil phosphorus availability and soybean response to phosphorus starter fertilizer - Rosolem, Ciro Antonio [UNESP]; Merlin, Alexandre (Sociedade Brasileira de Ciência do Solo, 2014)
Phosphorus fixation in tropical soils may decrease under no-till. In this case, P fertilizer could be surface-spread, which would improve farm operations by decreasing the time spend in reloading the planter with fertilizers. In the long term, less soluble P sources could be viable. In this experiment, the effect of surface-broadcast P fertilization with both soluble and reactive phosphates on soil P forms and availability to soybean was studied with or without fertilization with soluble P in the planting furrow in a long-term experiment in which soybean was grown in rotation with Ruzigrass (Brachiaria ruziziensis). No P or 80 kg ha-1 of P2O5 in the form of triple superphosphate or Arad reactive rock phosphate was applied on the surface of a soil with variable P fertilization history. Soil samples were taken to a depth of 60 cm and soil P was fractionated. Soybean was grown with 0, 30, and 60 kg ha-1 of P2O5 in the form of triple phosphate applied in the seed furrow. Both fertilizers applied increased available P in the uppermost soil layers and the moderately labile organic and inorganic forms of P in the soil profile, probably as result of root decay. Soybean responded to phosphates applied on the soil surface or in the seed furrow; however, application of soluble P in the seed furrow should not be discarded. In tropical soils with a history of P fertilization, soluble P sources may be substituted for natural reactive phosphates broadcast on the surface. The planting operation may be facilitated through reduction in the rate of P applied in the planting furrow in relation to the rates currently applied.

A fixação de fósforo em solos tropicais pode ser diminuída sob plantio direto. Nesse caso, o fertilizante poderia ser aplicado na superfície do solo, o que melhoraria o rendimento operacional pela diminuição do reabastecimento da semeadora com fertilizantes. Em longo prazo, fontes de P menos solúveis poderiam ser viáveis. Nesse experimento, o efeito da aplicação de P em superfície, tanto o fosfato solúvel como reativo, sobre as formas de P no solo e a disponibilidade para a soja foram estudados em combinação com a aplicação de P solúvel nos sulcos de semeadura, em um experimento de longa duração, onde a soja foi cultivada em rotação com braquiária (Brachiaria ruziziensis). Fertilizantes fosfatados foram aplicados na superfície de um solo com histórico de aplicações de P, nas doses 0,0 e 80,0 kg ha-1, na forma de superfosfato triplo ou fosfato Arad. Amostras de solo foram tomadas até 60 cm de profundidade, e o P do solo foi fracionado. A soja foi cultivada com 0, 30 e 60 kg ha-1 de P2O5 como superfosfato triplo aplicado no sulco da semente. Ambos os fertilizantes aplicados em superfície aumentaram o P disponível nas camadas superiores do solo e as formas moderadamente lábeis orgânica e inorgânica de P no perfil do solo, provavelmente como resultado do apodrecimento radicular. A soja respondeu aos fosfatos aplicados na superfície do solo ou no sulco de semeadura; no entanto, a aplicação de P solúvel no sulco não deve ser descartada. Em solos tropicais, com uma história de fertilização fosfatada, fontes de P solúveis podem ser substituídas por fosfatos naturais reativos aplicados à superfície do solo. A operação de semeadura pode ser agilizada pela redução da taxa de P aplicada ao sulco da sementeira, em relação às doses que são empregadas atualmente.
Disponibilidade de fósforo no solo e resposta da soja ao fertilizante aplicado no sulco de semeadura
Keywords: adubação; Brachiaria ruziziensis; fosfatos; fertilidade do solo; fertilization; Brachiaria ruziziensis; phosphates; soil fertility